Variación morfométrica en octocorales del género Pacifigorgia (Octocorallia: Gorgoniidae) (2020)
The taxonomic identification of octocorals is based on morphological characters, known for their high plasticity with the environment. This hinders the delimitation and identification of species, which translates in biases in the estimations of local and regional diversity, population abundance and physiological tolerance, among others. In order to recognize and quantify the effect of depth in some morphological characters of the genus Pacifigorgia, two taxonomically well-defined species, P. bayeri and P. cairnsi, were employed, comparing colonies from shallow (3-5 m) and deep (18-20 m) zones in the Gulf of Chiriquí, Panamanian Pacific. The external characters were evaluated from scaled images of the colonies, and the internal ones on confocal microscopy images of four types of sclerites. Following a nested mixed model in PERMANOVA and PERANOVA test, it was found that, externally, both species had a significant variation in the number of calices/cm with depth, although in a different direction, higher in the shallow zone for P. cairnsi and higher in the deep zone for P. bayeri. In addition, P. cairnsi had the widest mesh diameter in the deep zone. Internally, only P. cairnsi varied significantly with the depth in the length of almost all sclerites. Both species, although do not converge in their morphological response with depth, they show a highly significant variation between colonies of the same depth. Finally, some of these taxonomic characters, although plastic, did not generate visually perceptible variations that could have an impact on the taxonomic recognition of the species.